THE EFFECT OF TRADE SHOW SUPPORT ON TRADE PERFORMANCE: A STUDY ON EXPORTİNG FİRMS FROM TURKEY (Third Sector Social Economic Review, 2021)
Among the incentives given by the government to encourage exports, trade show support plays a crucial role in raising the export volumes of companies. This study examines the impact of trade show support on export volumes on a sample of exporting firms in Turkey. The study utilizes the export volumes and the trade show support of exporting firms from the Metal, Jewelry, Mining, Steel, Petrochemical, and Electric industries that applied for international trade show support to the Turkish Government between January 2014 and December 2018. We obtained the data from the official records of the Turkish Exporter Assembly, an umbrella organization founded to promote export. The cross-sectional dimension of the data consists of 3,027 firms, and the time dimension comprises 5 periods, which brings the total number of observations to 15,135. We conducted a panel data analysis with two fixed-effects and one random-effects model to estimate the effect of support on export. Results indicated that trade show supports affect the export rates of firms even though the effect size is small. A dollar increase in trade show support is associated with an almost ten-dollar increase in export. This means that an average trade show support, which is around $16 thousand, is associated with an almost $150 thousand increase in export. The impact of support on export varies by industry. To raise the efficiency, the amount of support can be increased in line with the export rates of the industries in which companies operate.
Keywords: Trade Show Support; Export; International Trade